(related to Fig 2) Changes in behavioral readouts as a function of laser power in the easy discrimination task. - Lilia Kukovska (22683586) (2025)
A) Average discrimination performance, d’, B) hit rate, and C) false alarm rate for all time window conditions. D) Normalized average discrimination performance, d’, in the ‘entire’ window for sessions with lower hit rate (> 0.95). Shading, 95% CI of bootstrap distribution. Data is normalized by subtracting the value of the 0 power level during 0–2 s of stimulus onset. The same normalization method is applied across all normalized data plots regardless of the stimulation window duration. E) Normalized false alarm rate in the ‘entire’ window. Color lines, individual mice (N = 10, 41 sessions). F) Normalized discrimination performance, d’, in the ‘early’ window. Color lines, individual mice (N = 10, 37 sessions). G) Average discrimination performance, d’, in three mice, where high laser power (2 mW/mm2) was used to silence the ‘early’ window (6 sessions). As expected, two of three mice showed impaired performance. H) Average running speed for ‘go’ (continuous) and ‘no-go’ (interrupted) conditions for the mouse which retained high performance when the ‘early’ window was silenced at 2 mW/mm2. Running was delayed relative to stimulus presentation. In all plots, except D), error bars or shading indicate SEM. (TIFF)